Associations between aerobic exercise levels and physical and mental health outcomes in men with bone metastatic prostate cancer: a cross‐sectional investigation. (20th September 2016) - Zopf, E.M.; Newton, R.U.; Taaffe, D.R.; Spry, N.; Cormie, P.; Joseph, D.; Chambers, S.K.; Baumann, F.T.; Bloch, W.; Galvão, D.A.
Abstract : Cancer patients with bone metastases have previously been excluded from participation in physical activity programmes due to concerns of skeletal fractures. Our aim was to provide initial information on the association between physical activity levels and physical and mental health outcomes in prostate cancer patients with bone metastases. Between 2012 and 2015, 55 prostate cancer patients (mean age 69.7 ± 8.3; BMI 28.6 ± 4.0) with bone metastases (58.2% >2 regions affected) undertook assessments for self‐reported physical activity, physical and mental health outcomes (SF‐36), objective physical performance measures and body composition by DXA. Sixteen men (29%) met the current aerobic exercise guidelines for cancer survivors, while 39 (71%) reported lower aerobic exercise levels. Men not meeting aerobic exercise guidelines had lower physical functioning ( p = .004), role functioning (physical and emotional) ( p < .05), general health scores ( p = .014) as well all lower measures of physical performance ( p < .05). Lower levels of aerobic exercise are associated with reduced physical and mental health outcomes in prostate cancer patients with bone metastases. While previous research has focused primarily in those with non‐metastatic disease, our initial results suggest that higher levels of aerobic exercise may preserve physical and mental health outcomes in prostate cancer patients with bone metastases. Clinical Trial Registry: Trial Registration: ACTRN12611001158954